Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Avinci Wedding Planner Yogyakarta - Shifa, Laula Linatus; Citrawati, Luh Putu; Sumadi, I Gede (Journal of Event and Convention Management, 2025)
Avinci Wedding Planner is a well-known wedding service provider in Yogyakarta City that has a variety of wedding packages. This study aims to analyze the influence of service quality on consumer satisfaction at Avinci Wedding Planner Yogyakarta. This study uses a quantitative method approach with a population of 194 consumers and a sample of 66 respondents determined using the Slovin Technique. Data collection using questionnaires, interviews, and documentation studies. The testing of the research instrument used validity test and reliability test with SPSS version 26. The data analysis techniques used were normality test, heterokedasticity test, simple linear regression analysis, f test, t test, and determination coefficient. The results showed that the quality of service had a positive and significant influence on consumer satisfaction with a t- calculated value greater than the t-table (9.065 > 1.99714) and a significance level of 0.000 < 0.05. The determination coefficient showed that service quality contributed 56.2% to consumer satisfaction, with 43.8% influenced by other variables. The reliability dimension and the assurance dimension received the highest score (4.39), while the responsiveness dimension with an average score of (4.34) scored the lowest. These findings help Avinci Wedding Planner to optimize the improvement of service aspects that have a significant effect on customer satisfaction.